Biomarkers for knee osteoarthritis: new technologies, new paradigms. (August 2015) - Spain, Lucy; Rajoub, Bashar; Schlüter, Daniela K; Waterton, John; Bowes, Mike; Shark, Lik-Kwan; Diggle, Peter; Goodacre, John
There is a paucity of biomarkers in knee osteoarthritis (OA) to inform clinical decision making, evaluate treatments, enable early detection and identify people who are most likely to progress to severe OA. The absence of biomarkers places considerable limitations on the design of research studies, and is a barrier toward applying the principles of stratified medicine to knee OA. Here we describe key principles and processes of biomarker development and focus on two promising areas that draw upon technologies that have only relatively recently been developed for quantitative applications in clinical research, namely 3D MRI and acoustic emission. While still at an early stage, results to date show promising potential to open up interesting new paradigms in this field.